Investigation of GHG emission sources and reducing GHG emissions in a municipal wastewater treatment plant. Issue 5 (19th August 2019) - Demir, Özlem; Yapıcıoğlu, Pelin
Abstract: Global warming and the greenhouse effect are two of the most important environmental problems. Carbon dioxide, methane, and nitrous oxide emissions are the main greenhouse gas emissions in wastewater treatment plants. In this study, the greenhouse gas emission sources in a wastewater treatment plant were determined. Direct (from fossil fuel combustion, methane emissions, and process emissions of the other greenhouse gases) and indirect emissions (primarily from electricity use) in the plant were monitored. The optimum influent characteristics and operating conditions have been defined by using Monte Carlo simulation to minimize the emissions. The results revealed that the highest direct greenhouse gas emission was observed in August with the value of 23.328 kg CO2 ‐eq d –1 and the lowest emission was 7.56 kg CO2 ‐eq d –1 measured in January. The aeration tank is a major source of greenhouse gas emissions. Indirect emission has occurred because of the anaerobic digester but the biogas has been cogenerated in the plant, so it has been ignored for the calculation. According to the simulation study, if the plant is operated under optimum operating conditions, it can emit the lowest amount of greenhouse gas emissions. The optimum removal values required for the minimum greenhouse gas emissions are 79% for chemical oxygen demand, 75% for biochemical oxygen demand, and 82% for total suspended solid. The optimum operating conditions for the aeration tank, which is the major source of emission, are 5.33 h of hydraulic retention time, 0.215 d of solid retention time, and 0.999 for food/microorganisms. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.